(untitled) (Boca Raton, Fla., 2002)
DNA Arrays: Technologies and Experimental Strategies offers a view of different aspects of this rapidly developing technology, including oligonucleotide and electrochemical arrays. Distinguished investigators from academia and industry provide up-to-date insights into methodological fundamentals of construction of DNA arrays, optimization of hybridization conditions, the use of expression data in bioinformatics, software tools, and the application of microarray technology for drug discovery.
Keywords: DNA microarrays,Vi mạng DNA